Implementasi Moderasi Beragama Bagi Dosen dan Mahasiswa Program Studi Pendidikan Agama Islam IAIN Parepare - Mukhtar Mas'ud (LPPM Institut Pendidikan Nusantara Global, 2025)
The implementation of religious moderation for students in the Islamic Education programme at IAIN Parepare is an important step in the academic field. Students learn and apply religious moderation in their interactions with fellow students, lecturers, and others, both on and off campus. This helps students understand the importance of peace and tolerance in religion. There are nine key principles in religious moderation. First, humanity, which emphasises mutual respect. Second, the common good, where individuals should be beneficial to others. Third, justice, meaning avoiding unilateral decisions. Fourth, balance, meaning impartiality. Fifth, obedience to the constitution, which means following government rules. Sixth, national commitment, which means having a patriotic attitude. Seventh, tolerance, which means accepting differences. Eighth, anti-violence, which means not engaging in violent acts. Ninth, respect for local traditions. The urgency of religious moderation is to change students' knowledge so that they become more tolerant and humanistic. This is expected to foster mutual respect among students, lecturers, and the community. The implications of this research include opportunities for students to learn religious moderation, a shift in attitude from apathy and radicalism to tolerance, and improved understanding among various parties around the campus.